Peer accompaniment processes and online educational assistance during COVID-19 - Niño Carrasco, Shamaly Alhelí (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The universities implemented virtual support and tutorial programs to reduce repetition and dropout rates during Covid-19. Teacher-student accompaniment schemes have been documented for the most part, but little has been said about other modalities such as peer accompaniment. Under this scenario, an exploratory design was aimed to identify the types of educational assistance deployed during the pandemic within a peer tutoring program at a Mexican university. The results show that the most requested help revolves around the socio-emotional factor of learning.